ROLE OF MICROBIOTA-GUT-BRAIN AXIS IN AUTISM SPECTRUM DISORDER (International Seven Journal of Health Research, 2025)
Background: This narrative literature review shows a close link between autism spectrum disorder and the severity of gastrointestinal symptoms, as there is a two-way communicative linking known as the gut-brain axis, and a large amount of research shows the importance of a balanced microbiota to guarantee normal development and sustainment of brain function. Methods: A systematic review was performed utilizing the PubMed (Medline) database to explore literature published within the last 6 years, focusing on studies investigating the correlation between the gut-brain axis and autism spectrum disorder, with a specific emphasis on the gut microbiota. Results: Some studies findings demonstrate a decrease in bacterial diversity and also the influence of microbial metabolites associated with the development of ASD and the harshness of the symptoms. An imbalance in the gut microbial flora can result in dysbiosis, leading to diseases and overproduction of proinflammatory cytokines, affecting nutrition and immune responses. Although many studies involving microbiota transfer, vitamin A, the use of probiotics, and other kinds of nourishment are being held, there are no definitive or effective therapies for ASD yet. Conclusions: More studies are needed to understand the connection between the gut-microbiome-brain axis and ASD, as well as how dietary changes can improve ASD symptoms.